Senegal : Impact on Tobacco Use and Tax Revenues - World Bank Group (World Bank, Washington, DC, 2018)
This study has three main objectives. First, it aims to assess the impact of tobacco excise tax increases over 2012-14 on prices, consumption levels, and tax revenues in Senegal, as well as the response by tobacco companies to such increases. Second, the report models the potential impact of two scenarios involving future excise tax increases on tobacco products in Senegal, and considers alterations in the structure of tobacco excise taxation. Finally, it offers policy options to government authorities.